Child Abandonment in 19th Century Lisbon: The Provenance and Distribution of Foundlings Through a GIS Lens - Vieira Paulino, Joana (European Journal of Geography, 2025)
In Portugal, until the late 1860’s, child abandonment was an anonymous, legal, and generalized practice. The Santa Casa da Misericórdia de Lisboa (SCML) was responsible for the guardianship of Lisbon’s abandoned children, the Portuguese capital and largest city. Nevertheless, the character of such a practice led to increasing numbers. A debate then emerged and became more vigorous over the mid-century, culminating in the decree of 1867. This replaced the wheels, a wooden cylinder which rotated to allow anonymous abandonment, with controlled and justified admissions, the generalization of lactation subsidies, and policing around the institutions. Where did foundlings come from and where were they sent when raised by external wet nurses after their abandonment? Was there a spatial pattern? To produce a spatial and visual representation of this distribution and coverage to address the research questions, this analysis relies on the SCML quantitative reports and on SIGMA, a GIS-database designed to depict the evolutions in Portuguese administrative divisions. We conclude that most foundlings came from Lisbon and, in later years, from those Lisbon parishes hosting the popular and working classes, and later preferably distributed to wet nurses living in the countryside, thereby achieving the institution’s goals. Highlights: The end of anonymous child abandonment in Portugal and a case study of 19th century Lisbon. The provenance of abandoned children at the municipal (Portugal) and parish (Lisbon) levels through a GIS. Distribution of foundlings to external wet nurses & teachers of crafts at the municipal level (Portugal) through a GIS.